PERAN PERUSAHAAN SUB-SEKTOR MAKANAN DAN MINUMAN DALAM MENDORONG PERTUMBUHAN EKONOMI DI INDONESIA - Sukmadiana, Muhammad Yusup; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The food and beverage industry is one of the leading sectors that contributes significantly to Indonesia’s economy. This sub-sector has consistently demonstrated growth in recent years, supported by increased domestic consumption, product diversification, and competitiveness in international markets. As a vital pillar in the national economic structure, companies in the food and beverage sub-sector not only contribute to increasing the Gross Domestic Product (GDP) but also create job opportunities and attract investments from both domestic and foreign sources. This study aims to analyze the strategic role of food and beverage sub-sector companies in driving economic growth in Indonesia. The research method adopts a qualitative approach based on literature studies, referring to secondary data from official reports, government policies, and previous research findings. The results indicate that although this sector makes a substantial contribution, there are challenges to address, such as fluctuations in raw material prices, global competition, and digital transformation. In conclusion, companies in the food and beverage sub-sector play a key role in Indonesia’s economic growth and hold great potential to support sustainable development.